Monodomain liquid crystal elastomers and elastomeric gels: Improved thermomechanical responses and phase behaviour by addition of low molecular weight LCs - Brown, David; Das, V.; Allen, R.; Styring, P. (Elsevier Science SA, 2007)
Large monodomain-liquid crystal elastomer films have been prepared using mechanical alignment, either as pure materials or as gels doped with low molecular weight chiral liquid crystals. The thermomechanical strain behaviour of the resulting materials has been studied over a range of temperatures. The largest thermal strains have been achieved when the mechanical alignment was carried out in the smectic A phase, just below the transition to the apparent isotropic liquid phase. The pure elastomers exhibit thermomechanical responses over broad temperature ranges (ca. 60 ?C), however the elastomer gels doped with a low molecular weight LC exhibit significantly sharper thermomechanical responses over a narrower temperature range (ca. 15 ?C).